NEUROPATHIC PAIN IN PATIENT WITH POST OPERATIVE SCHWANNOMA: A CASE REPORT PRIMARY INTRADURAL EXTRAMEDULLAR SPINAL CORD TUMOUR - Santoso, Widodo Mardi; Nurlela, Siti; Marhaendraputro, Eko Arisetijono; Rahmawati, Dessika (Malang Neurology Journal, 2019)
Majority of spinal cord tumour is a benign tumour with symptoms are due to spinal cord compression. One of the symptoms that are often difficult to treat is a sensory deficit. The authors report a case of primary intradural extramedullar spinal cord tumour in 57-year-old man. This tumour was presenting symptoms of chronic low back pain, gradual progressive inferior paraplegia, and sensory deficit on both legs. MRI thoracal showed intradural lesion at Th 4-5-6, with isointensity on T1-weighted images and hyperintensity-isohomogen on T2-weighted images. The tumour was completely resected, and histopathology examination revealed schwannoma types. Patient showed a clinical improvement in motoric function noticeable after surgery, but showed sensory deficits sequelae requiring therapy for neuropathic pain.